Presence and extent of lymphovascular invasion in surgical stage I squamous cell carcinoma of the cervix: a comprehensive, international, multicentre, retrospective clinicopathological study - Stolnicu, Simona; Allison, Douglas; Tessier-Cloutier, Basile; Momeni-Boroujeni, Amir; Hoang, Lien; Ieni, Antonio; Felix, Ana; Terinte, Cristina; Pesci, Anna; Mateoiu, Claudia; Hodgson, Anjelica; Guerra, Esther; et al. (Pathology, 2025)
The aim of this study was to determine whether the presence and extent of lymphovascular invasion (LVI) is prognostic in surgical stage I cervical squamous cell carcinoma (SCC). All available tumour slides and/or paraffin blocks from 426 patients with stage I cervical SCC treated surgically with curative intent were collected from 18 institutions and retrospectively analysed. Presence and extent of LVI (focal <5 spaces, extensive ≥5 spaces) were assessed on scanning magnification in large haematoxylin and eosin slide sets in 366 cases. Progression-free survival (PFS) was calculated as the time from surgery to first progression or death or last follow-up, whichever occurred first. Overall survival (OS) was defined as the time from surgery to death or last follow-up. Clinicopathological and statistical analyses were performed on 97 patients with the International Federation of Gynecology and Obstetrics (FIGO) 2018 stage IA and 329 patients with stage IB SCC of the cervix. LVI, both focal and extensive, was more frequent in stage IB than in stage IA (p<0.001). Patients with stage IB carcinomas with extensive LVI had worse PFS [hazard ratio (HR) 2.86; 95% confidence interval (CI) 1.49, 5.49; p=0.005] and OS (HR 2.88; 95% CI 1.38, 6.02; p=0.012) than those with focal or no LVI. In stage IA, in contrast, the presence and extent of LVI did not associate with PFS (p=0.926) or OS. Extensive LVI was not statistically correlated with PFS and OS in substages IA1, IA2 or IB2. PFS (HR 3.7; 95% CI 1.61, 8.46; p<0.001) and OS (HR 4.18; 95% CI 1.58, 11.04; p=0.002) in stage IB1, and PFS (HR 7.78; 95% CI 0.87, 69.82; p=0.039) in stage IB3 were diminished in the presence of extensive LVI. In conclusion, in patients with FIGO stage I cervical SCC, the presence and extent of LVI has prognostic significance in stage IB carcinoma, and quantifying LVI is recommended.
Keywords: senioři; Neoplasm Invasiveness; spinocelulární karcinom; senioři nad 80 let; prognosis; Retrospective Studies; Prognosis; lymph node metastasis; Middle Aged; lymfatické metastázy; cervix uteri; Adult; nádory děložního čípku; Lymphatic Metastasis; Aged, 80 and over; Neoplasm Staging; stage; ženské pohlaví; prognóza; retrospektivní studie; Humans; squamous cell carcinoma; invazivní růst nádoru; lidé středního věku; staging nádorů; Uterine Cervical Neoplasms; dospělí; Carcinoma, Squamous Cell; Female; Aged; Cervix Uteri; lidé; lymphovascular invasion